Escherichia coli concentrations and antibiotic resistance profile in nearshore waters of Manila Bay, Philippines - Palmares, Aaron Jan; Morabe , Jianina Lauryne; Parazo, Ma. Liezl; Maddara, Mary Izabelle; Rodas, Dyve John; Placino , Erica; Rodriguez III, Reynato; Nicolas, Cybelle Alyxes (Ecological Questions, 2026)
This study investigates the extent of microbial contamination and antimicrobial resistance (AMR) in the nearshore waters of Manila Bay, Philippines, a region heavily impacted by urbanization and anthropogenic pollution. Forty water samples were collected from five coastal sites and analyzed for physicochemical parameters, Escherichia coli (E. coli) concentrations, and antimicrobial susceptibility. Results revealed E. coli levels averaging 17,300 CFU/100 mL, which significantly exceeded national water quality standards and indicated severe and sustained fecal contamination. Physicochemical conditions (mean turbidity of 10.8 NTU, pH 7.35, low dissolved oxygen at 1.46 mg/L, and high conductivity at 22,509 µS/cm) support short-term bacterial survival. Antimicrobial susceptibility testing of 40 E. coli isolates showed resistance to at least one antibiotic in 70% of isolates, with 20% classified as multiple antibiotic-resistant (MAR) and 17.5% as multidrug-resistant (MDR). Ampicillin resistance was most common (60%), followed by gentamicin (25%), cotrimoxazole (22.5%), and ciprofloxacin (12.5%). No extended-spectrum beta-lactamase (ESBL)-producing strains were detected. Correlation analyses found significant associations between E. coli concentration and turbidity (positive) and conductivity (negative), but no significant link between resistance levels and physicochemical parameters, suggesting resistance development is driven by other environmental or genetic factors. These findings underscore the urgent need for integrated water quality management, stricter pollution control, and enhanced AMR surveillance to protect public health and the marine environment. The study highlights Manila Bay as a critical hotspot for microbial pollution and antibiotic resistance, warranting immediate action and continued monitoring.